Access to the NHS by telephone and Internet during an influenza pandemic: an observational study. Issue 2 (3rd February 2014) - Rutter, Paul; Mytton, Oliver; Ellis, Benjamin; Donaldson, Liam
Abstract : Objectives: To examine use of a novel telephone and Internet service—the National Pandemic Flu Service (NPFS)—by the population of England during the 2009–2010 influenza pandemic. Setting: National telephone and Internet-based service. Participants: Service available to population of England (n=51.8 million). Primary and secondary outcome measures: Primary: service use rate, by week. Numbers and age-specific and sex-specific rates of population who: accessed service; were authorised to collect antiviral medication; collected antiviral medication; were advised to seek further face-to-face assessment. Secondary: daily mean contacts by hour; proportion using service by telephone/Internet. Results: The NPFS was activated on 23 July 2009, operated for 204 days and assessed 2.7 million patients (5200 consultations/100 000 population). This was six times the number of people who consulted their general practitioner with influenza-like illness during the same period (823 consultations/100 000 population, rate ratio (RR)=6.30, 95% CI 6.28 to 6.32). Women used the service more than men (52.6 vs 43.4 assessments/1000 population, RR1 21, 95% CI 1.21 to 1.22). Among adults, use of the service declined with age (16–29 years: 74.4 vs 65 years+: 9.9 assessments/1000 population (RR 7.46 95% CI 7.41 to 7.52). Almost three-quarters of those assessed met the criteria to receive antiviral medication (1 807 866/2 488 510; 72.6%). Most of the people subsequently collected this medication, although more than one-third did not (n=646 709; 35.8%). Just over one-third of those assessed were advised to seek further face-to-face assessment with a practitioner (951 332/2 488 504; 38.2%). Conclusions: This innovative healthcare service operated at large scale and achieved its aim of relieving considerable pressure from mainstream health services, while providing appropriate initial assessment and management for patients. This offers proof-of-concept for such a service that, with further refinement, England can use in future pandemics. Other countries may wish to adopt a similar system as part of their pandemic emergency planning.